Impact of reputation and brand image on the intention to purchase educational services in private universities in Perú - Erazo-Ordoñez, Yessica (2024)
In Peru, higher education has experienced significant growth due to the fact that public universities are unable to meet the demand of many young people who wish to pursue a university degree. In this context, the reputation and brand image of private universities are key factors in students' choice of where to pursue their academic education. The objective of this study is to evaluate the influence of brand image and reputation on the purchase intention. This study has a quantitative approach, a nonexperimental cross-sectional design, and an explanatory level through a structural equation model. The study sample is made up of 381 students from 3 private universities in the capital of Peru. The results of the theoretical model were accepted because the RMSEA and SRMR values are very close to zero, the CFI =1, Chi-square (X^2)= 0.000116, and the (df)=1. Also, a high correlation was found between reputation and brand image (β=0.793). It is concluded that a strong brand image together with a favorable reputation contribute considerably to explain the variability in the purchase intention and the successful performance of Peruvian private universities.